A Comprehensive Review on the Supraclavicular Flap for Head and Neck Reconstruction. Issue 6 (4th June 2022) - Jahromi, Alireza Hamidian; Horen, Sydney R.; Miller, Emily J.; Konofaos, Petros
Abstract: The supraclavicular artery flap (SCF) is a highly vascularized fasciocutaneous flap overlying the shoulder. The flap was first described in 1979 by Lamberty but did not gain popularity until much later due to lack of a reliable technique. The main advantages of using the SCF include avoiding microsurgical techniques, requiring only a single-stage operation, shorter operative time compared with alternative options, and a wider patient population including those with comorbidities who may be excluded from more extensive operations including free flaps surgeries. The SCF has been successfully performed on individuals with advanced age, poor nutrition, cachexia, obesity, diabetes, tobacco use, severe chronic obstructive pulmonary disease, hypertension, coronary artery disease, peripheral vascular disease, supraventricular tachycardia, atrial fibrillation, heart failure, asthma, and steroid use. The largest disadvantages of the SCF include the possibility of distal tip necrosis, size limitation without pre-expansion, and a moderately visible donor site scar. The following review and meta-analysis of the SCF details its use historically as both an island and a pedicle flap, and its application in head and neck reconstruction.